Atomically-thin In(OH)3 nanosheets towards photocatalytic CO2-to-CO conversion - Kang, Wei Kiat (Nanyang Technological University, 2020)
In this work, Indium compounds photocatalyst will be explored due to their high catalytic activities for photooxidation and photoreduction ability under visible light irradiation. This project will cover and concentrate on the synthetization of Indium-containing nanostructured 2D materials that demonstrate photocatalytic activity under solar irradiation wave spectrum with the key process of reducing CO2. Investigation was carefully carried out via X-Ray diffraction, UV-visible absorption spectroscopy, Atomic force measurement, scanning electron microscope (SEM) and Transmission electron microscope (TEM) to determine the phase compositions, optical properties and morphologies of the photocatalyst. In this chapter, properties, preparation, and function of indium compound nanomaterials used as photocatalysis for the reduction of CO2 will be systematically summarized, which is favourable for understanding the functionality and developing the potential photocatalyst applications.